Agro-Tourism as a Source of Additional Income in Agriculture - Musaxanov Qazixon Abdulxakim o‘g‘li (Genius Journals, 2023)
The article highlights issues such as agrotourism, places for overnight stays and recreation related to agriculture and its surroundings, positive features of agrotourism are directly related to all the values that the rural environment brings.
Keywords: rural population; quality of life; rural entrepreneurship